The use of communication technology channel in agricultural development by Malaysia Muda Agricultural Development Authority (MADA) - Mahamood, Ahmad Fahmi; Mohammed, Rosli; Ahmad, Mohd Khairie (Lyceum of the Philippines University - Batangas, 2016)
Innovation in agriculture is generally defined as the implementation of ideas, products, practices, processes, new services or apparent improvements in certain environments with attention to benefit the society and the individuals within (Rogers, 1995).The use of communication technology as the innovation in the agricultural information delivery channel among farmers is still low, especially among the developing countries.This phenomenon has sparked researcher’s initiatives to study the agricultural information delivery channel, particularly in agricultural development activities among the farmers under the auspices of Muda Agricultural Development Authority (MADA). In soliciting the decision-making phase of accepting the innovation, there are a few drawbacks of the channel as it was shown by Innovation Diffusion Theory.The rapid development of communication technology has led to two-way, interactive and easy-access media channel, which previously dashingly dependent on conventional media and agricultural agency.The study variables include the relative advantages, the trialibility, the suitability, the complexity, and the observability as had been described by Everett. M.Rogers. Additionally, variables such as effort expectancy, performance expectancy, social influences and facilitating condition are taken into account as to facilitate the dissemination of information on the paddy plantation. This study will use quantitative method in which opinions through a questionnaire will be collected. A total of 398 farmers was involved as the respondents of the study.The quantitative data were analysed using SPSS Version 21.The study is expected to improve the use of communication technology channel in paddy plantation to gain better and more knowledge on paddy plantation in order to increase rice production.